URINARY DISCOMFORTS IN PATIENTS AFTER RADICAL PROSTATECTOMY - S. Kh. Al’-Shukri; I. A. Ananiy; R. E. Amdiy; I. V. Kuz’Min (Вестник хирургии имени И.И. Грекова)
The authors showed the result of complication treatment of lower urinary tracts in 128 patients with localized prostate cancer. The patients underwent radical prostatectomy. Urinary discomforts included enuresis, urinary incontinence in postoperative period. Abnormalities of urine outflow due to urethral stricture were revealed in 6 (4,6%) patients by the 6 month after operation. These complications required surgical treatment. Urinary incontinence was noted in 20 (15,6%) patients in this period. It was stressful urinary incontinence in 16 (12,6%) and urgent - in 4 (3%). Patents with stressful urinary difficulty were advised to use the conservative treatment (pelvic floor muscle training and electrostimulation), but in case of inefficiency- surgical treatment